Pengaruh Leverage, Jumlah Penduduk dan Umur Pemerintah Daerah terhadap Kinerja Keuangan Pemerintah Daerah: Studi Empiris pada Kabupaten/Kota Provinsi Sumatera Barat Periode 2016-2020 - Muhammad Raihanul Alfi; Vita Fitria Sari (Universitas Negeri Padang, 2023)
This study aims to determine the effect of leverage, population and age of local government on local government financial performance. The population in this study is Regency/City in West Sumatra Province in 2016-2020. This study uses secondary data. The sampling technique used the total sampling method with a sample of 19 districts/cities with a period of 5 years. This study uses multiple linear regression analysis on hypothesis testing. The results showed that the leverage and age of the local government had a positive and significant effect on the financial performance of the local government. While the population has a negative and significant effect on the financial performance of local governments.